Pengaruh Fernand Braudel terhadap Kajian Sejarah Maritim di Indonesia - Rohman, Muhammad Habibur (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2021)
Fernand Braudel is one of the most influential historians in modern historiography. Braudel's works are considered to provide a new perspective for writing in modern historiography. As his work entitled The Mediterranean and the Mediterranean World in the Age of Philip II is considered a revolutionary study that is different from the conventional / traditional historiography tradition. This study aims to examine the role and influence of Fernand Braudel's thoughts in writing modern history. The method used is a literature review with a unit of analysis of his figures and works, that is Fernand Braudel and his work The Mediterranean and the Medoterranean World in the Age of Philip II. The research results show that Braudel's work introduces something new, namely